Your Creative Writing Masterclass : featuring Austen, Chekhov, Dickens, Hemingway, Nabokov, Vonnegut, and more than 100 Contemporary and Classic Authors /: featuring Austen, Chekhov, Dickens, Hemingway, Nabokov, Vonnegut, and more than 100 Contemporary and Classic Authors. (2012) - Wolff, Jürgen
No abstract available